Integrating Knowledge Management into Marketing for Enhanced Decision-Making and Performance - Abbas, Muhammad (Advances in Business & Industrial Marketing Research, 2024)
The integration of knowledge management (KM) into marketing strategies has become increasingly vital for organizations striving to enhance decision-making processes and overall performance in today's dynamic business landscape. This study aims to explore the multifaceted nature of KM integration in marketing contexts and its implications for organizational success.The researches design employed a systematic literature review to synthesize insights from diverse perspectives and shed light on key determinants of KM effectiveness. Findings reveal that organizational readiness, user acceptance, and system usability emerge as critical factors influencing the effectiveness of KM in supporting marketing decision-making. Organizational culture, leadership support, and technological infrastructure play pivotal roles in shaping KM initiatives and driving organizational performance outcomes. The implications of this study underscore the importance of addressing challenges related to organizational culture, leadership support, and technological infrastructure to maximize the benefits of KM in marketing contexts. By adopting proactive measures and a holistic approach to KM implementation, organizations can leverage their knowledge assets more effectively and gain a competitive edge in the marketplace.